The Conflict Between the Two Main Belgian Nationalities. Its Correlation With the Case of a Partnership Between University, Public and Private Iniatives, and Its Result in the New City of Louvain-La-Neuve - Panagiota Tsolakaki; Ioannis Fragopoulos (European Regional Science Association (ERSA), 2006)
This paper deals with contemporary planning projects that are correlated with community-university partnerships. It studies the ways in which the socio-spatial and national conflict in Belgium in the '60 led to an innovative resolution which is correlated with planning projects (the transformation of rural space) and a new form of contemporary 'new cities'. The main subject of work is the new city named Louvain-la-neuve that was created in order to accomodate the French-speaking university of Leuven after the linguistic conflict of 1968 and the social problem of the difficulties of the coexistence of two different nationalities. Through this project of the city in question, which was mobilized by the administration of the university (UniversitéCatholique de Louvain), the French-speaking Belgian government also aimed in the creation of a new pole of development in the French-speaking region (Wallonie) which would force the development of the whole region and would restore the French-speaking community in the limelight (as it was in an earlier time). More specifically, the research surveys the characteristics of the project according to some parameters: b) the role of the university in the planning processes c) the way that education consists the motivating force of a city and creates agglomeration economies d) and the planning theory in practice and the knowledge of university in planning matters, e)the results of the project in the national and regional economy in the local society and in the sustainability of the city. The local research including living in the area for several months took place in the year 2001 and the main research was made between September 2003 and August 2004 and the analysis of the data followed. The research was based on the local research as well as in two structured interviews with two off the main staff of both the French and Dutch-speaking administration committee of the university of Leuven, visual and photographical survey and group discussions with the local population permanent and temporary, and collection of all possible planning and policy documents as well as surveys concerning the project and the city. The outcome of the research shows the way in which the well-known Belgian national problem resulted in a partnership between the community and the university and in the creation of a new contemporary city that in our days tries to survive and ameliorate its environment through the knowledge-theory and the resources that the university can continuously ensure for the city's development. The research has shown a new innovative approach of the Belgian planning processes that is deeply correlated to a socio-political problem.
Keywords: 330